Effects of Developmental Deltamethrin Exposure on White Adipose Tissue Gene Expression. Issue 2 (11th February 2013) - Armstrong, Laura E.; Driscoll, Maureen V.; Donepudi, Ajay C.; Xu, Jialin; Baker, Angela; Aleksunes, Lauren M.; Richardson, Jason R.; Slitt, Angela L.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Deltamethrin, a type II pyrethroid, is a widely used insecticide. The purpose of this study was to determine whether perinatal deltamethrin exposure altered the expression of adipogenic and lipogenic genes in white adipose tissue (WAT) in adult pups. C57BL/6 pregnant mice were administered 0, 1, or 3 mg/kg of deltamethrin orally every 3 days throughout gestation and lactation. Offspring were weaned on postnatal day 25, and WAT was collected from 5‐month‐old male mice. Perinatal deltamethrin exposure decreased the mRNA expression of adipogenesis‐related transcription factors Pparγ, Cebpα, and lipogenic genes Srebp1c, Acc‐1, Cd36, Lpl, Scd‐1; along with Nrf2 and target genes Nqo1 and Gclc at the 1 mg/kg treatment. Cytokine expression of Fas/Tnf‐R and Cd209e at the 1 mg/kg treatment was significantly decreased, and expression of Tnf, Cd11c, and Fas/Tnf‐R was decreased at the 3 mg/kg treatment. Developmental deltamethrin exposure did not overtly affect body weight or adipose weight, but decreased mRNA expression of specific genes that may potentially disrupt normal adipogenesis and lipid and glucose metabolism if the offspring are challenged by changes in diet or environment. © 2013 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:165‐171, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21471